Controlling and Detection of Public Street Light Using Wireless Connection - Herpurnomo, Adnantio; Suwarno, Djoko Untoro (Institut Teknologi Dirgantara Adisutjipto, 2018)
The public street light used to create good conditions for road users. The public street lamps must continue to be maintained to keep working properly. Currently, maintenance of street lighting is still done manually. In this research, a system was designed and implemented to detect lamp damage and control lights remotely using the WeMos D1 microcontroller. This system uses two LDRs as sensors and relays to activate the lights. The first LDR is used to detect ambient light. The second LDR is used to detect lamp conditions. Light control and detection use internet wireless networks and WeMoS D1 as a web server. The system can turn on and turn off the lights automatically, detect the condition of the lamps, and show the intensity of the light environment. Distance to control via a wifi hotspot using a computer is 72m and 20m for a mobile phone.